2006
DOI: 10.1080/00268970500417861
|View full text |Cite
|
Sign up to set email alerts
|

Valence ionization spectra of 4π-electron molecules with low-lying satellites involving n–π* and π–π* transitions

Abstract: The valence ionization spectra up to 25-30 eV of the 4p-electron molecules, butadiene, acrolein, glyoxal, methylenecyclopropene and methylenecyclopropane were investigated by the SAC-CI method. Accurate theoretical assignments of the spectra were given and further the natures of the low-lying satellites were examined. Acrolein and glyoxal have the low-lying satellites of n À1 p À1 p à and n À2 p à states and the outermost satellites are lower than the p À2 p à state of butadiene. However, their intensities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The valence MOs are n + , n − , CvO −, and CvO + in the order of increasing IP experimentally proposed by Turner, 37 which is in agreement with the present SAC-CI results. The previous systematic SAC-CI study 65 on the valence shell of 4-conjugated molecules also gave the same ordering for these states. Therefore, the excitations corresponding to → * transition are relatively higher in energy than those of n → * ; the order of valence shell is important for the correct assignments of the excited states.…”
Section: State/naturesupporting
confidence: 67%
“…The valence MOs are n + , n − , CvO −, and CvO + in the order of increasing IP experimentally proposed by Turner, 37 which is in agreement with the present SAC-CI results. The previous systematic SAC-CI study 65 on the valence shell of 4-conjugated molecules also gave the same ordering for these states. Therefore, the excitations corresponding to → * transition are relatively higher in energy than those of n → * ; the order of valence shell is important for the correct assignments of the excited states.…”
Section: State/naturesupporting
confidence: 67%
“…However, numerous theoretical and experimental studies showed that there are certain classes of compounds where satellites can appear also in the outer-valence region. These are systems containing heavier atoms, like transition-metal complexes [21,22], or π-electron systems [23,24,25,26,27], which have lowenergy virtual orbitals. Here we will concentrate on the latter class of systems and will investigate the impact of the low-lying satellites on the electron dynamics following outer-valence ionization of some organic unsaturated nitroso compounds [27].…”
Section: Introductionmentioning
confidence: 99%